PENGARUH WORKING CAPITAL TURNOVER, DEBT TO CAPITAL RATIO, DAN OPERATING CYCLE TERHADAP KINERJA KEUANGAN PADA PT HM SAMPOERNA Tbk PERIODE 2015 – 2024 - Dimas Permana Putra; Hestu Nugroho Warasto (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Abstract. This study aims to determine the effect of Working Capital Turnover (WCTO), Debt to Capital Ratio (DCR), and Operating Cycle (OC) on Financial Performance measured using Return on Capital Employed (ROCE) at PT Hm Sampoerna Tbk for the period 2015-2024. The method in this study is descriptive quantitative. Data analysis methods used in this study include: Descriptive Statistical Test, Classical Assumption Test (Normality Test, Multicollinearity Test, Autocorrelation Test, and Heteroscedasticity Test), Multiple Linear Regression Test, Hypothesis Test (t Test (Partial) and F Test (Simultaneous)), and Determination Coefficient Test. The results of this study indicate that the Working Capital Turnover (WCTO) variable partially has no significant effect on Financial Performance because the calculated t value is 0.175 <t table 2.447 and the sig value is 0.875> 0.05. The Debt to Capital Ratio (DCR) variable partially has a negative and significant effect on Financial Performance, as the calculated t-value is -3.020 > t-table value of 2.447, and the sig. value is 0.023 < 0.05. The Operating Cycle (OC) variable partially has a negative and significant effect on Financial Performance, as the calculated t-value is -2.470 > t-table value of 2.447, and the sig. value is 0.048 < 0.05. Simultaneously, Working Capital Turnover (WCTO), Debt to Capital Ratio (DCR), and Operating Cycle (OC) have a significant positive effect on Financial Performance at PT Hm Sampoerna Tbk, as the calculated F-value is 14.058 > F-table value of 4.76, with a significance level of 0.004 < 0.05. Keywords: Working Capital Turnover, Debt to Capital Ratio, Operating Cycle,